STRATEGI KOMUNIKASI PERSUASIF MAHASISWA ILMU KOMUNIKASI UNIVERSITAS MUHAMMADIYAH KOTABUMI DALAM MEMEMPROMOSIKAN PROGRAM STUDI MELALUI MEDIA SOSIAL - Tedi Setiawan; Marini; Hagi Julio Salas (Komsospol, 2022)
Communication is a crucial part of social life within a community. In this digital era, communication and interaction between individuals can take place through various means, one of which is social media. In many human activities, effective communication is essential to ensure that messages reach the recipients successfully. Persuasive communication is particularly important for influencing recipients in specific contexts, such as promoting the communication science program at UMKO. This research adopts a qualitative approach with interview data collection techniques. The purpose of persuasive communication by UMKO communication science students in promotions is to attract the interest of prospective students to the communication science program itself. Promotion efforts are carried out through social media platforms like Facebook and Instagram. Persuasive communication on social media proves to be quite effective, given the widespread use of these platforms for obtaining desired information. Through persuasive communication in promotional activities, it aims to influence prospective students pursuing higher education at the university level to choose the communication science program.